Taeniasis among Refugees Living on Thailand–Myanmar Border, 2012 - Ellen J. McCleery; Prapas Patchanee; Pornsawan Pongsopawijit; Sasisophin Chailangkarn; Saruda Tiwananthagorn; Papaspong Jongchansittoe; Anchalee Dantrakool; Nimit Morakote; Hnin Phyu; Patricia P. Wilkins; John Noh; Christina R. Phares; et al. (Emerging Infectious Diseases, 2015)
We tested refugee camp residents on the Thailand–Myanmar border for Taenia solium infection. Taeniasis prevalence was consistent with that for other disease-endemic regions, but seropositivity indicating T. solium taeniasis was rare. Seropositivity indicating cysticercosis was 5.5% in humans, and 3.2% in pigs. Corralling pigs and providing latrines may control transmission of these tapeworms within this camp.